Using the size independent discriminant analysis to distinguish the species of Myliobatis Cuvier (Batoidea: Myliobatidae) from Brazil - Aguiar, Aline Augusto; Gallo, Valéria; Valentin, Jean Louis (Zootaxa, 2004)
The two only species of Myliobatis Cuvier, that occur in the Brazilian coast, Myliobatis freminvillii Lesueur and Myliobatis goodei Garman, have great similarity in external morphology and possess few diagnostic characters that allow easy identification. In order to discriminate these two species, 34 specimens of M. freminvillii and 19 of M. goodei were measured and twenty morphometric characters were taken from each specimen. The residuals of a previous regression analysis performed on all morphometric variables relative to the disc width were used in the Size Independent Discriminant Analysis. All specimens were correctly allocated to their respective taxa. The analysis showed a clear separation of the specimens, forming two well-defined distinct groups. The fifth interbranchial distance (5ID) was the variable with the highest standardized discriminant coefficient value. The fifth interbranchial distance (5ID)-Internarial distance (IND) and fifth interbranchial distance (5ID)-Mouth width (MW) were the proportions that showed better differentiation between Myliobatis species.